Hypertension Exercise: A Non-Pharmacological Strategy for Reducing Blood Pressure in Adults with Hypertension - Wahdini, Rizqa; Sibualamu, Khalida Ziah; Chairunisa, Ratu (LPPM Universitas Dhyana Pura, 2025)
Hypertension is recognized as a leading contributor to cardiovascular diseases and is frequently labeled a